Pooled analysis of progression-free survival and overall survival in phase II clinical trials of breast cancer - Shobnam, Sohana (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2024.